PENGEMBANGAN PROFESIONALISME GURU DALAM PEMBELAJARAN PADA KURIKULUM MERDEKA DI SMK NEGERI 3 BALIKPAPAN - Indriawati, Prita; Prasetya, Kiftian Hady; Susilo, Ganjar; Sari, Indra Yusnita; Hayuni, Sajaratun (LPPM Universitas Kahuripan Kediri, 2023)
The purpose of this article is to find out the development of teacher professionalism in learning the independent curriculum. The method used in this research is qualitative. Data obtained by observation and interviews with teachers. The independent curriculum that is implemented at SMK Negeri 3 Balikpapan is emphasized on subjects. Support from professional organizations greatly supports teachers in preparing for learning to implement the independent curriculum. Teachers receive training in learning the independent curriculum, the core of the independent curriculum, namely the Independent Curriculum, is here to perfect the implementation of the Curriculum. Implementation at SMK Negeri 3 Balikpapan on the independent learning curriculum for teachers catches up with literacy and numeracy. For students, the independent curriculum can provide solutions for improving the curriculum, before the curriculum can be implemented in stages according to the readiness of each school.